Acute compressive stress activates RHO/ROCK-mediated cellular processes. (2nd September 2020) - Boyle, Sarah T.; Kular, Jasreen; Nobis, Max; Ruszkiewicz, Andrew; Timpson, Paul; Samuel, Michael S.
ABSTRACT: The ability to rapidly respond to applied force underpins cell/tissue homeostasis. This response is mediated by mechanotransduction pathways that regulate remodeling and tension of the actomyosin cytoskeleton to counterbalance external forces. Enhanced extracellular matrix tension hyper-activates mechanotransduction and characterizes diseased states such as cancer, but is also required for normal epidermal regeneration. While the impact of extracellular matrix tension on signaling and cell biology are well appreciated, that of acute compressive force is under-studied. We show here that acute compressive force applied to cells and tissues in a native 3-dimensional context elevates RHOA-GTP levels and increases regulatory myosin phosphorylation, actomyosin contractility and tension via ROCK. In consequence, cell proliferation was increased, as was the expression of regulators of epithelial-mesenchymal transition. Pharmacological inhibition of ROCK abrogated myosin phosphorylation, but not RHOA activation. Our results strongly suggest that acute compressive stress impairs cellular homeostasis in a RHO/ROCK-dependent manner, with implications for disease states such as cancer.